2021
DOI: 10.1021/acs.langmuir.1c00309
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Counterion Binding to Swelling of Polyelectrolyte Brushes

Abstract: The effect of binding strength of counterions with the polyelectrolyte chain to the swelling of polyelectrolyte brushes is studied, by investigating the swelling of both the polycation and polyanion in response to the variation of the salt concentration under the change of counterion’s identity. Two polyelectrolyte brushes grafted on solid substrates are adopted: the cationic poly [2-(methacryloyloxy)­ethyltrimethyl ammonium] (PMETA-X, X = F, Cl, Br, and I) and the anionic polystyrene sulfonate (M-PSS, M = Li,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 61 publications
5
22
0
Order By: Relevance
“…Excellent mechanical properties of the hydrogel broaden its application range and make it possible for its long-term role in marine antifouling and oil pollution prevention. Hydrophilic hydrogels are easily swollen in water, thereby affecting the mechanical properties. As shown in Figure , the PVA/Gly hydrogel presented poor mechanical strength (0.58 MPa). After TA was introduced into the hydrogel through hydrogen bond interaction, the mechanical strength of the hydrogel increased to 1.30 MPa.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Excellent mechanical properties of the hydrogel broaden its application range and make it possible for its long-term role in marine antifouling and oil pollution prevention. Hydrophilic hydrogels are easily swollen in water, thereby affecting the mechanical properties. As shown in Figure , the PVA/Gly hydrogel presented poor mechanical strength (0.58 MPa). After TA was introduced into the hydrogel through hydrogen bond interaction, the mechanical strength of the hydrogel increased to 1.30 MPa.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Accordingly, specific counterion effects in these systems refer to the ability of counterions to influence these two swelling mechanisms. Although it has been experimentally observed that specific counterion effects on the swelling behavior of polyelectrolyte brushes follow the Hofmeister series, various explanations, for example, ion hydrophobicity/hydrophilicity and ion-pair formation between counterions and immobile charges on the polyelectrolytes, have been used to rationalize the observations. For example, Murdoch et al suggested that ion hydrophobicity can solely explain the specific ion effects in a hydrophobic weak polyelectrolyte brush. On the other hand, Zimmermann et al and Higaki et al demonstrated that ion-pair formation with weakly hydrated anions reduces the thickness of strong polyelectrolyte brushes at low ionic strength (where the ion osmotic effect is pronounced).…”
Section: Introductionmentioning
confidence: 99%
“…This tendency agrees with a previous report on the ion penetration and swelling dynamics of a PSS brush on a QCM chip. [ 48 ] Each trend follows an empirical scaling‐law: τnormalG=Aλ+0α1 where A is the time constant at a small ion size limit, and α is the ideality factor that indicates the degree of deviation from free diffusion at α = 0. The time constant ratio A ex /A in has only a slight variation from unity, indicating the gate response is almost symmetric over a wide range of cation species.…”
Section: Resultsmentioning
confidence: 99%